Double tunnel technique reduces technical failure during POEM in cases with severe submucosal fibrosis - Nabi, Zaheer; Ramchandani, Mohan; Chavan, Radhika; Basha, Jahangeer; Reddy, Manohar; Darisetty, Santosh; Reddy, Nageshwar D. (Endoscopy International Open, 2021)
Background and study aims Submucosal fibrosis (SMF) is one of the major reasons for technical failure during per-oral endoscopic myotomy (POEM). In this study, we aimed to evaluate the impact of double tunnel technique (DT-POEM) on the technical success of POEM in cases with severe SMF.Patients and methods Data from patients with achalasia in whom SMF was encountered during POEM from Jan 2013 to Jan 2020 at our center were retrospectively evaluated. The technical success and adverse events (AEs) were analyzed and compared between cases with SMF who underwent POEM via single tunnel versus DT-POEM technique.Results A total of 1,150 patients underwent POEM during the study period. There were 14 technical failures (1.2 %). SMF and severe SMF was found in 104 (9 %) and 21 (1.8 %) patients, respectively. The majority of patients (17, 80.9 %) with severe SMF had type I achalasia. Overall, technical failures occurred in 14 cases (1.2 %) and severe SMF resulted in the majority of the technical failures (10, 71.4 %). DT-POEM was utilized in 11 cases (52.4 %) with severe SMF. The median procedure time with DT-POEM was 150 minutes (85–210). There were no major AEs and DT-POEM was technically successful in all the patients. The technical success of POEM in cases with SMF improved after the adoption of the double tunnel technique (98.4 % vs 68.3 %, P = 0.0001).Conclusions Severe SMF is the most common reason for technical failure during POEM. DT-POEM improves the technical success rates of POEM in patients with severe SMF.